A32: Low Vitamin D Status is Associated with Avascular Necrosis: An Atherosclerosis Prevention in Pediatric Lupus Erythematosus Substudy. Issue 11 (March 2014) - Gurion, Reut; Tangpricha, Vin; Yow, Eric; Schanberg, Laura E.; McComsey, Grace; Robinson, Angela; ,
Abstract : Background/Purpose: Avascular necrosis (AVN) can result in significant morbidity. Previous studies suggest that AVN is associated with systemic lupus erythematosus (SLE) and corticosteroid treatment. Hypovitaminosis D has been postulated to play a role in bisphosphonate‐associated osteonecrosis of the jaw. Using frozen serum and demographic data from the Atherosclerosis Prevention in Pediatric Lupus Erythematosus (APPLE) trial, we conducted an exploratory analysis to assess associations between AVN and demographics, SLE disease activity and vitamin D deficiency, defined as serum 25‐hydroxyvitamin D [25(OH)D] <20 ng/mL. Methods: APPLE trial participants were randomized to placebo or atorvastatin. Frozen serum collected at baseline was used to measure 25(OH)D levels by chemiluminescent assay (IDS, LTD). Univariable analysis of APPLE data at baseline to 3 years was performed using chi‐squared test for categorical baseline variables and Wilcoxon signed rank test for continuous variables. Results: Samples were available for 201/221 APPLE participants. 17/201 (8.4%) either had a history of (n = 9) or developed AVN during the study period (n = 8). Vitamin D deficiency, minority status, southern latitude, elevated triglycerides, and a history of hypertension and/or glomerulonephritis were associated with the presence or development of AVN (1 ). Body mass index, presence of antiphospholipid antibodies, SLEDAI, SLE disease duration and corticosteroid use were not associated with AVN. Conclusion: This is the first report of vitamin D deficiency associated with AVN in pediatric lupus. There was a trend towards lower vitamin D levels in subjects who developed AVN during the 3 years of the trial, but this was not statistically significant likely due to low numbers. AVN has devastating consequences, and its pathogenesis is likely multi‐factorial. Unlike other studies, no association was seen between steroid use and AVN. This association does not prove causation, but suggests future avenues of study and may suggest a method of prevention for AVN.